Contingency Approach to Performance Measures Design - Nita, Bartłomiej (Podejście uwarunkowań sytuacyjnych do projektowania mierników dokonań, 2010)
The author deals with the problem of performance measures design methodology on the basis of contingency theory. In the first part of the article the general overview of contingency framework was described and the typology of contingency factors was proposed in respect of both external and internal variables. In the second part the detailed study of the contextual factors was analyzed. In particular the linkage between critical success factors and performance measures design was examined. Finally the adjusting of the performance measures to the organizational structure was elaborated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 103-114
Keywords: performance measurement; contingency theory